P.068 Abnormal fatty acid metabolism is a feature of spinal muscular atrophy. (5th June 2019) - Deguise, M; Beauvais, A; Baranello, G; Pileggi, C; Mastella, C; Tierney, A; Chehade, L; Leone, A; De Amicis, R; Battezzati, A; De Repentigny, Y; Warman Chardon, J; et al.
Abstract : Background: Spinal muscular atrophy (SMA) is a children's neuromuscular disorder. Although motor neuron loss is a major feature of the disease, we have identified fatty acid abnormalities in SMA patients and in preclinical animal models, suggesting metabolic perturbation is also an important component of SMA.Methods: Biochemical, histological, proteomic, and high resolution respirometry were used.Results: SMA patients are more susceptible to dyslipidemia than the average population as determined by a standard lipid profile in a cohort of 72 pediatric patients. As well, we observed a non-alcoholic liver disease phenotype in apreclinical mouse model. Denervation alone was not sufficient to induce liver steatosis, as a mouse model of ALS, did not develop fatty liver. Hyperglucagonemia in Smn 2B/-mice could explain the hepatic steatosis by increasing plasma substrate availability via glycogen depletion and peripheral lipolysis. Proteomic analysis identified mitochondrion and lipid metabolism as major clusters. Alterations in mitochondrial function were revealed by high-resolution respirometry. Finally, low-fat diets led to increased survival in Smn 2B/-mice.Conclusions: These results provide strong evidence for lipid metabolism defects in SMA. Further investigation will be required to establish the primary mechanism of these alterations and understand how they lead to additional co-morbidities in SMA patients.